Analysis of Effectiveness and Efficiency of Daihatsu De-18 Diesel Generator Maintenance Implementation Time on The Ship MV CSSC Gladstone - Ivan, Muh.; Hanafie, Ahmad (PT. Hafasy Dwi Nawasena, 2025)
Diesel generator engine maintenance on ships is an important activity to maintain the performance and operational reliability of ships. The effectiveness and efficiency of maintenance implementation time has a direct impact on the availability of generators to meet maximum electricity needs in various operational conditions. This study aims to analyze the effectiveness and efficiency of diesel generator engine maintenance time on board the MV CSSC Gladstone. Maintenance time data was obtained from ship maintenance records and analyzed to gain a better understanding of the maintenance process. The results showed that effective and efficient maintenance time plays an important role in maintaining smooth ship operations and minimizing generator downtime. Suggestions put forward include planning regular maintenance schedules, continuous monitoring and evaluation, utilizing monitoring technology, regular training for maintenance personnel, and collaboration with manufacturers or experts in the field of maintenance. By considering these suggestions, it is expected that ships can improve the effectiveness and efficiency of maintenance time and maintain their overall operational performance and reliability